2008
DOI: 10.1897/08-148.1
|View full text |Cite
|
Sign up to set email alerts
|

Vitellogenin as a biomarker for estrogenic effects in brown trout, Salmo trutta: Laboratory and field investigations

Abstract: The sensitivity of juvenile brown trout towards estrogenic chemicals (17beta-estradiol [E2], estrone [E1], 17alpha-ethinylestradiol [EE2], 4-tert-octylphenol [OP], and n-butylparaben [BP]) was tested in laboratory experiments with plasma and liver vitellogenin concentrations as endpoints. Vitellogenin concentrations were also assessed in juvenile brown trout collected in streams affected by agricultural runoff and discharges from scattered houses in the open land. In the laboratory, juvenile brown trout were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
2
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 62 publications
3
30
2
2
Order By: Relevance
“…The range of VTG levels and the magnitude of VTG increase in the current study were similar to those reported in a marine study on wild flounder in Japan [34] and in a freshwater study on brown trout in Denmark [35]. The range and magnitude were also similar to the lower end of those reported for wild flounder in the United Kingdom or the Netherlands [36,37] and in freshwater studies involving either wild roach [38] or caged rainbow trout [39] held for three to four weeks downstream of sewage effluent outfalls in the United Kingdom.…”
Section: Discussionsupporting
confidence: 89%
“…The range of VTG levels and the magnitude of VTG increase in the current study were similar to those reported in a marine study on wild flounder in Japan [34] and in a freshwater study on brown trout in Denmark [35]. The range and magnitude were also similar to the lower end of those reported for wild flounder in the United Kingdom or the Netherlands [36,37] and in freshwater studies involving either wild roach [38] or caged rainbow trout [39] held for three to four weeks downstream of sewage effluent outfalls in the United Kingdom.…”
Section: Discussionsupporting
confidence: 89%
“…Propylparaben elicited vitellogenin induction in Japanese medaka at 9.9 mg/L, but lower concentrations were not tested [20]. Additionally, butylparaben has been shown to induce plasma vitellogenin production in male brown trout at 134 mg/L and higher [45]. Although studies have not observed estrogenic effects at levels that are at concentrations that have been observed in effluent or surface waters, exposure values are limited in number and in types of sites sampled.…”
Section: Discussionmentioning
confidence: 97%
“…Exposure of several species of fish to estrogen and estrogenic compounds has also caused a reduction in GSI and an inhibition of the sperm cell development (Jobling et al 1996;Van den Belt et al 2001. In a recent field survey it has been confirmed that in second year Danish brown trout, male (5.6 ± 4.6; n = 17) GSI is generally higher, but also much more variable than female (0.28 ± 0.13; n = 17) GSI (Bjerregaard et al 2008). …”
Section: Gonadal Developmentmentioning
confidence: 97%